Effect of Job Satisfaction on Employee Job Performance Mediated by Affective Commitment - Juhana, Dudung (Jurnal Computech & Bisnis (e-journal), 2019)
Job satisfaction is one of the goals to be achieved by organizations. This goal is to support the desire of employees to work better and can have a strong commitment to completing their duties. This study investigates the effect of job satisfaction on employee job performance mediated by affective commitment. The survey method used in answering research formulations. Non-parametric suppressors with Partial Least Square (PLS) are used to prove the purpose of the study. The survey conducted at one government office in the city of Bandung by distributing questionnaires to 70 employees. The results showed that the affective commitment of employees could improve the completion of their tasks better. This factor will encourage them to work harder. With the satisfaction of employees who fulfilled driven by a high commitment to the organization will lead to high employee task performance.